Tingkat Partisipasi Masyarakat Lokal dalam Pengelolaan Ekowisata di Kampung Saporkren Distrik Waigeo Selatan Kabupaten Raja Ampat - Ellen Tanati; Wahyudi Wahyudi; Anton Silas Sinery (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2020)
Saporkren village at Raja Ampat Islands is well-known for international and domestic icons for community based ecotourism in West Papua Province. This research is designed to investigate the levels of participation, functions and intensity of five groups of respondents (leader, interested group, family members, women, and teenager), influenced factors and benefits received from participation are also investigated. The results indicated that levels of participation of five groups of respondents are classified into extremely inactive (1-25) with an average for their index PEI of less than 25, and levels of participation for children are absent. Leaders had function in planning with intensity for total control and decision making. Other respondent of interested groups, family members and women had funstions in implementation, maintenance, and distribution with intensity for decision making, consultation, and information. However, five groups of respondents are absent in management function and initiation action of intensity involvement. Counseling from official government (70.8%), invitation from local officer (41.7%), and income generating (37.5%) are three main factors influenced the local community interested in ecotourism participation. Various direct and indirect benefits from ecotrourism management are confirmed such as famous ecotourism destination, local entrepreneur (homestay, handycraft, local cuisine), tour guides, local nature conservation guards, motorist, and the others. Three important issues for ecotourims based community in Saporkren village are management, initiation action, and absence of the teenagers in levels of participation.